Graph Composer: music composition from graph design - Souza, Pedro; Rolla, Vitor; Ayres, José Eduardo; Sánchez, José Ezequiel (Anais do Simpósio Brasileiro de Computação Musical (SBCM); 2019: Anais do XVII Simpósio Brasileiro de Computação Musical, 2019)
The Graph Composer is an app that allows the user to compose music through the design of a graph. You can create or modify an existing graph, listen and modify the composition in real time. Insert new nodes and connect them, change the corresponding note by clicking over the node and selecting a new one from the scale, define it’s duration over time and select a decoration to change the sound sequence.